Arbitrary (Contractual, Credit) Coercion (Compelling) in the Condition of Legal Omission - Muhammad Salehi Mazandarani; Payam Muhammadi Mirazizi (آموزه‌‌های فقه مدني)
The civil law has not taken any action regarding the sanctity of the condition of legal omission, and this has caused a difference of opinion among the jurists. Some have commented on the annulment, some on the validity, and others on the invalidity of the legal act of impermissible (forbidden) act. This research tries to strengthen the recent theory and for this purpose, suggests the theory of arbitrary (contractual, credit) coercion. According to this theory, the sanction of the person who is responsible to perform a condition which is against him (Arabic: مَشْروطٌ عَلیه) and he/she violated that condition in this type of condition, according to the primary rule is compelling and the impossibility of the coercion (compelling) of the person who is responsible to perform a condition is not imagined; because, the coercion (compelling) of the person who is responsible to perform a condition is arbitrary (contractual), which means that the legal act of impermissible (forbidden) act is concluded in a contractual way. In other words, coercion must be of the form of the desired act, and since the mentioned act is arbitrary (contractual, credit), the manner of coercion must also be arbitrary. This coercion (compulsion) without the need to perform any material or legal action is done spontaneously. Coercion has been realized, when, there is no effect legally on the person who is responsible to perform a condition which is against him and promised it, and there is no need for any further action. Accepting the validity of the forbidden legal act, in addition to the inconsistency with the intention of the parties, means the permission to the breach of contract and the effective termination of the contract. The theory of nullity is also incompatible with the foundations of our legal system.